Breastfeeding Initiation Associated With Reduced Incidence of Diabetes in Mothers and Offspring. Issue 5 (November 2016) - Martens, Patricia J.; Shafer, Leigh Anne; Dean, Heather J.; Sellers, Elizabeth A. C.; Yamamoto, Jennifer; Ludwig, Sora; Heaman, Maureen; Phillips-Beck, Wanda; Prior, Heather J.; Morris, Margaret; McGavock, Jonathan; Dart, Allison B.; et al.
Abstract : OBJECTIVE: To examine associations between breastfeeding initiation and subsequent diabetes among First Nations (indigenous people in Canada who are not Métis or Inuit) and non–First Nations mothers and their offspring with and without gestational diabetes mellitus (GDM). METHODS: This retrospective database study included 334, 553 deliveries (1987–2011) in Manitoba with up to 24 years of follow-up for diabetes using population-based databases. Information of breastfeeding initiation before hospital discharge was obtained from hospital abstracts recorded by nurses in postpartum wards. Cox proportional hazard models were applied to examine the association between breastfeeding initiation and risk of diabetes in mothers and their offspring. RESULTS: Breastfeeding initiation was recorded in 83% of non–First Nations mothers and 56% of First Nations mothers ( P <.001). Breastfeeding initiation was associated with a reduced risk of incident (later developed) diabetes in non–First Nations mothers without GDM (hazard ratio [HR] 0.73 [or −27% of risk], 95% confidence interval [CI] 0.68–0.79), non–First Nations mothers with GDM (HR 0.78 or −22% of risk, CI 0.69–0.89), First Nations mothers without GDM (HR 0.89 or −11% of risk, CI 0.81–0.98), and First Nations mothers with GDM (HR 0.82 or −18% of risk, CI 0.73–0.92) with 24 years of follow-up or less. With 24 years of follow-up or less, breastfeeding initiation was associated with a 17% lower risk of youth-onset type 2 diabetes in offspring (HR 0.83, CI 0.69–0.99, P =.038). The association between breastfeeding initiation and subsequent diabetes in mothers and offspring was independent of family income, rural residence, First Nations status, GDM, parity, gestational hypertension, and age of the mother. CONCLUSION: Breastfeeding initiation is associated with a reduced risk of diabetes among women and their offspring in Manitoba. The results suggest that breastfeeding might be a potentially modifiable factor to reduce the risk of diabetes in both First Nations and non–First Nations women and children. Abstract : Breastfeeding initiation is associated with a reduced risk of postpartum diabetes among women and type 2 diabetes in their offspring in Manitoba, Canada.